2007
DOI: 10.4081/ijas.2007.s2.409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of indigenous anatolian water buffalo breed using microsatellite dna markers

Abstract: One indigenous water buffalo population to Anatolia was characterised with 11 cattle autosomal microsatellite loci. A set of 4 cattle microsatellite loci was found to be polymorphic in the Anatolian buffalo genome. Genotyping of these polymorphic microsatellite loci revealed alleles ranging from 3 to 9. The observed heterozygosity ranged from 0.550 to 0.775 and the expected heterozygosity ranged from 0.494 to 0.815. The FIS value within each locus, changed from –0.101 to 0.205. Total FIS was 0.043 indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
19
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 2 publications
11
19
3
Order By: Relevance
“…The Jafarabadi population showed the most deviation with 10 markers, while the other populations showed disequilibrium with five to eight markers. These results are in agreement with those reported by Soysal et al (2005), in Turkey and Flamand et al …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The Jafarabadi population showed the most deviation with 10 markers, while the other populations showed disequilibrium with five to eight markers. These results are in agreement with those reported by Soysal et al (2005), in Turkey and Flamand et al …”
Section: Resultssupporting
confidence: 94%
“…The mean of observed heterozygosity (H o ) and expected heterozygosity or gene diversity (H e ) are close to those reported by Soysal et al (2005), Arora et al (2004), Flamand et al (2003) and Navani et al (2002). Moioli et al (2001) found values significantly lower in buffaloes from Greece, Italy and Egypt.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…These results are a preliminary step for characterization of Anatolian buffalo. Characterization of this buffalo under various aspect is very important as the high degree of genetic variability, tested by means of microsatellite markers (Soysal et al, 2007), induces to think that there is a good perspective of genetic improvement. and suggests that this buffalo may be an important tool to increase productivity both in small farms located in villages systems and in medium-large farms.…”
Section: Results and Conclusion -mentioning
confidence: 99%